2018
DOI: 10.1186/s12967-018-1707-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognostic value of paraoxonase 1 in the recurrence and metastasis of hepatocellular carcinoma and establishment of a liver-specific predictive model of survival

Abstract: BackgroundHepatocellular carcinoma is a malignant tumor with a highly invasive and metastatic phenotype, and the detection of potential indicators associated with its recurrence and metastasis after surgical resection is critical for patient survival.MethodsTranscriptome data for large cohorts (n = 1432) from multicenter sources were comprehensively analyzed to explore such potential signatures. The prognostic value of the selected indicators was investigated and discussed, and a comparison with conventional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Interestingly, GAST can also expresses in a group of primary human tumors, including neuronal, renal, and myogenic stem cell tumors [ 25 ], which suggest that GAST may play a previously unrecognized role in human CSC. Galanin and GMAP Prepropeptide (GAL) has been demonstrated to activate in human HCC, and it prefers to accumulate in the stromal tissue around the HCC cells [ 26 ]; Somatostatin (SST) is a kind of hormone that can inhibits the release of various secondary hormones; Paraoxonase 1 (PON1) was found to be a highly related predictor of recurrence and metastasis in HCC [ 27 ]; Production and Homeostasis of Lipoprotein(A) (LPA) can be impaired when liver cancer occurs [ 28 ]; and both the downregulation of PON1 [ 27 ] and alcohol dehydrogenase 4 (Class II), Pi polypeptide (ADH4) [ 29 ] can confers poor survival time of HCC. However, the relationship among these genes and CSC or stemness was seldom reported.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GAST can also expresses in a group of primary human tumors, including neuronal, renal, and myogenic stem cell tumors [ 25 ], which suggest that GAST may play a previously unrecognized role in human CSC. Galanin and GMAP Prepropeptide (GAL) has been demonstrated to activate in human HCC, and it prefers to accumulate in the stromal tissue around the HCC cells [ 26 ]; Somatostatin (SST) is a kind of hormone that can inhibits the release of various secondary hormones; Paraoxonase 1 (PON1) was found to be a highly related predictor of recurrence and metastasis in HCC [ 27 ]; Production and Homeostasis of Lipoprotein(A) (LPA) can be impaired when liver cancer occurs [ 28 ]; and both the downregulation of PON1 [ 27 ] and alcohol dehydrogenase 4 (Class II), Pi polypeptide (ADH4) [ 29 ] can confers poor survival time of HCC. However, the relationship among these genes and CSC or stemness was seldom reported.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the cfDNA adsorption rate is an indicator of possible potential malignant tumor efficacy monitoring and prognosis evaluation. However, its sensitivity and specificity in monitoring efficacy is low, and its recurrence diagnostic efficacy is similar to clinical tumor biomarkers such as CEA and AFP [41,42]. When the sensitivity increases, the specificity is significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has suggested that PON1 could serve as an important clinical indicator of cancer progression for a number of cancers such as lung cancer and breast cancer (Bobin-Dubigeon et al, 2015;Aldonza et al, 2017). Data in THPA database showed that the expression of PON1 in HCC is significantly higher than that in other tumors, and its down-regulated expression has been implicated to be a poor indicator for survival in patients with HCC (Yu et al, 2018). MAPK7 (mitogen-activated protein kinase 7) encodes extracellular-regulated protein kinase 5 (ERK5).…”
Section: Discussionmentioning
confidence: 99%